Leeds via Berlin Javier De Frutos, the new artistic director of Phoenix, takes on the West End - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Choreographer Javier De Frutos in conversation. PALABRAS CLAVE: Javier De Frutos, Rufus Norris, Kit Kat Club, Cabaret, Nazis.